Examining Behavioral Manifestations of Split Alliances in Four Couple Therapy Sessions. Issue 2 (3rd April 2022) - Friedlander, Myrna L.; Hynes, Kevin; Anderson, Shayne; Tambling, Rachel; Megale, Allison; Xu, Mengfei; Peterson, Emily K.
Abstract: We designed this theory-building study to discover how split alliances are manifested in couple therapy. From an archival database, we selected four cases in which the partners' self-reported alliances with the therapist were highly discrepant. An intensive analysis of each session was conducted to model the underlying therapeutic system based on interactional frequencies, a measure of interpersonal closeness, and identify alliance-related behaviors exhibited by clients and therapists using the multidimensional System for Observing Family Therapy Alliances. Results showed consistencies as well as variability across cases, largely reflecting the four (heterosexual) couples' pre-disposing problems and relational characteristics. Spatial maps of each session reflected the unbalanced alliance perceptions in two of the four cases. Whereas behavioral indicators of clients' engagement and emotional connection with their therapists varied widely, a problematic within-system alliance was observed in every case. Cross-blaming and discussion of an attachment injury were also observed across cases. While the therapists were largely engaging, affirming and supportive, in two split alliance sessions they displayed considerably more empathy for the male partner than the female partner. In many ways the results supported and extended the literature on alliances in general and split alliances in particular.